Oxford Handbooks Online 2014
DOI: 10.1093/oxfordhb/9780199686858.013.060
|View full text |Cite
|
Sign up to set email alerts
|

Traditional and New Principles of Perceptual Grouping

Abstract: Perceptual grouping refers to the process of determining which regions and parts of the visual scene belong together as parts of higher order perceptual units such as objects or patterns. In the early 20 th century, Gestalt psychologists identified a set of classic grouping principles which specified how some image features lead to grouping between elements given that all other factors were held constant. Modern vision scientists have expanded this list to cover a wide range of image features but have also exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 117 publications
(121 reference statements)
2
31
0
3
Order By: Relevance
“…This is a modern grouping principle (Palmer & Rock, 1994), which states that elements that are connected by other elements tend to be grouped together, and unlike most classical grouping principles that are intrinsicbased on some property of the elements themselves (e.g., color, location, shape)-it is an extrinsic grouping principle, in which grouping of several elements is based on their relations with contextual elements (e.g., Palmer & Beck, 2007). It has been demonstrated that this principle can overcome similarity by shape, and even the effect of proximity (Brooks, 2015;Palmer & Rock, 1994;Palmer, 1999). Thus, examining attentional demands for organizations involving the principle of element connectedness would provide additional and desired information concerning this principle.…”
Section: Experiments 3 4 Andmentioning
confidence: 99%
“…This is a modern grouping principle (Palmer & Rock, 1994), which states that elements that are connected by other elements tend to be grouped together, and unlike most classical grouping principles that are intrinsicbased on some property of the elements themselves (e.g., color, location, shape)-it is an extrinsic grouping principle, in which grouping of several elements is based on their relations with contextual elements (e.g., Palmer & Beck, 2007). It has been demonstrated that this principle can overcome similarity by shape, and even the effect of proximity (Brooks, 2015;Palmer & Rock, 1994;Palmer, 1999). Thus, examining attentional demands for organizations involving the principle of element connectedness would provide additional and desired information concerning this principle.…”
Section: Experiments 3 4 Andmentioning
confidence: 99%
“…Perceptual organization is the architecture studio of vision, which is in charge of fitting together the pieces of the retinal mosaic to build a tidy visual experience. The seminal work of Wertheimer (1923) described the main principles of perceptual grouping that determine what regions of an image constitute perceptual units or objects (Brooks, 2015), such as proximity, similarity, common fate, symmetry, parallelism, closure or good continuation. From the proposal of Palmer (1992Palmer ( , 1999, these classic Gestalt laws are classified as intrinsic grouping cues since they are based on built-in properties of the discrete elements (e.g., their shape, position), and a new set of extrinsic grouping principles which was added based on relationships between the discrete elements and other external elements that induce them to group.…”
Section: Introductionmentioning
confidence: 99%
“…Also, grouping by connectedness is the tendency of elements that are connected by other elements to be seen as part of the same group (Palmer & Rock, 1994). Prior evidence indicates that these principles can compete effectively against some of the classic Gestalt principles (Brooks, 2015). Remarkably, the ecological rationale behind connectedness arises from the fact that several parts of an object are frequently connected to one another despite showing a visual disparity in color or form (Brooks, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, these conditions can also be organized according to the hierarchical level of grouping they seem to tap into. First, in all four of these conditions, the line segments create some kind of generic spatial grouping (based on proximity and good continuation) – a rather crude, basic type of grouping, which is probably established at a relatively low level in the visual hierarchy (Brooks, ). Second, in the two experimental conditions, the actual physical connections between the line segments and the square boxes create two connection‐based grouping conditions, which can be distinguished from the control conditions (with none or altered connecting line segments) at a somewhat more fine‐grained level of detail, given some type of actual connection is present.…”
Section: Methodsmentioning
confidence: 99%